1998
DOI: 10.1093/jn/128.8.1355
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Synthesis Is Elevated in Fasting Cancer Patients with an Acute Phase Response

Abstract: The unusual amino acid composition of acute phase proteins may be relevant to our understanding of the mechanism of tissue wasting in chronic inflammatory disease. During periods in which demand for amino acids outstrips dietary supply, skeletal muscle protein may be mobilized to meet this demand. An imbalance in the amino acid composition of these proteins may thus be detrimental to the body's nitrogen economy. To address this problem, we have measured the synthetic rate of fibrinogen (perhaps the major acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 25 publications
3
78
1
2
Order By: Relevance
“…The negative correlation of the serum tryptophan level with IL-2 sRa and sTNF RI was compatible with a Th1 immune response (Mills et al, 1993;Diez-Ruiz et al, 1995) releasing interferon-g to induce tryptophan degradation (Murr et al, 2000). Cachexia studies in pancreatic cancer have suggested (Preston et al, 1998) that a tumour-associated acute phase protein response induces fibrinogen synthesis at the expense of skeletal muscle reserves. The greater aromatic amino acid (mostly tryptophan) content in fibrinogen compared with skeletal muscle proteins, may then result in tryptophan depletion.…”
Section: Discussionmentioning
confidence: 80%
“…The negative correlation of the serum tryptophan level with IL-2 sRa and sTNF RI was compatible with a Th1 immune response (Mills et al, 1993;Diez-Ruiz et al, 1995) releasing interferon-g to induce tryptophan degradation (Murr et al, 2000). Cachexia studies in pancreatic cancer have suggested (Preston et al, 1998) that a tumour-associated acute phase protein response induces fibrinogen synthesis at the expense of skeletal muscle reserves. The greater aromatic amino acid (mostly tryptophan) content in fibrinogen compared with skeletal muscle proteins, may then result in tryptophan depletion.…”
Section: Discussionmentioning
confidence: 80%
“…For example, interleukin-6, produced by the tumour or infiltrating inflammatory cells, is recognised as a growth promoter in bladder cancer (Okamoto et al, 1997;Andrews et al, 2002). Interleukin-6 also stimulates liver production of acute-phase proteins, such as Creactive protein, which increases the demand for certain amino acids, which, if limited in the diet, must be obtained from the breakdown of skeletal muscle Preston et al, 1998). In this way, the presence and magnitude of a chronic systemic inflammatory response may produce a progressive nutritional and functional decline, ultimately resulting in reduced survival.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that the presence of a chronic systemic inflammatory response, with its increased demand for specific amino acids for acute phase protein synthesis, promotes the degradation of available body protein including albumin (Preston et al, 1998;McMillan et al, 2001). Indeed, this relationship between nutritional decline, albumin concentrations and the systemic inflammatory response has recently been exploited to form a new prognostic score in patients with advanced non-small-cell lung cancer (Forrest et al, 2003).…”
Section: Discussionmentioning
confidence: 99%